2015
DOI: 10.1007/s00264-015-2814-7
|View full text |Cite
|
Sign up to set email alerts
|

Results of deformity correction in children with X-linked hereditary hypophosphatemic rickets by external fixation or combined technique

Abstract: Simultaneous correction of femoral and tibial deformities by means of circular external fixators is preferable. Application of a combined osteosynthesis allows to considerably reduce the duration of external fixation and decrease the number of complications. There were no recurrent deformities in parts of bone reinforced by intramedullary nails.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 34 publications
1
21
0
5
Order By: Relevance
“…We have hypothesized that intramedullary osteosynthesis could be realized with HA-coated wires available on our market and started to use them instead of regular nails in clinical practice for reinforcement of bone fragments stability in diaphyseal fracture repair, bone lengthening and deformity correction in combination with the Ilizarov external fixation [69]. We observed that bone formation and repair went on faster with their use [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have hypothesized that intramedullary osteosynthesis could be realized with HA-coated wires available on our market and started to use them instead of regular nails in clinical practice for reinforcement of bone fragments stability in diaphyseal fracture repair, bone lengthening and deformity correction in combination with the Ilizarov external fixation [69]. We observed that bone formation and repair went on faster with their use [7].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, flexible intramedullary nailing with thin wires, HA coated or uncoated, has been advocated for management of diaphyseal fractures, lengthening and deformity correction [69]. It was observed that the use of such wires stimulated bone reparation and reduced the total period of treatment in clinical settings.…”
Section: Introductionmentioning
confidence: 99%
“…Надо отметить, что в нашей серии с обычными ти-тановыми стержнями было отмечено 8 случаев такого осложнения [19]. С другой стороны, стабилизирующий эффект биоактивного покрытия мы наблюдали и при коррекции деформаций у детей с фосфат-диабетом [16].…”
Section: вопросы детской ортопедииunclassified
“…Было доказано, что высоко-дробное круглосуточное удлинение благоприятно влияет как на репаративный остеогенез, так и на функциональ-ную реабилитацию после лечения [13][14][15]. Другим спосо-бом, стимулирующим костное сращение при удлинении конечностей, является интрамедуллярное эластичное армирование, в том числе, с биоактивным покрытием [16][17][18][19][20]. Экспериментальные исследования показали, что интрамедуллярное введение эластичных стержней не нарушает целостности питательной артерии и, таким образом, не противоречит принципам метода Илизарова [14,21].…”
unclassified
See 1 more Smart Citation